ESEA Title III 1972 - PACE in Pennsylvania - Research and Information Services for Education, King of Prussia, PA.; Research and Information Services for Education, King of Prussia, PA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
This document is a collection of abstracts of all ESEA Title III educational innovation projects funded or operating in Pennsylvania during 1972. Each abstract contains the name of the local supporting agency, the project number, financial information, target population, major objectives, activities, evaluation design, findings to date, dissemination plan and progress toward adoption. Also included in the publication is a subject index (using ERIC descriptors), a grade level grid chart, an alphabetical list of school districts, and follow through cards for further information. (DP)
Sponsoring Agency: Pennsylvania State Dept. of Education, Harrisburg. Bureau of Planning and Evaluation.
Sponsoring Agency: Bureau of Elementary and Secondary Education (DHEW/OE), Washington, DC. Div. of Plans and Supplementary Centers.
Educational level discussed: Early Childhood Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Abstracts; Activities; Early Childhood Education; Educational Innovation; Educational Programs; Evaluation Methods; Federal Aid; Objectives; Socioeconomic Status; Student Characteristics; Elementary Secondary Education Act Title III